Campylobacter jejuni PflB is required for motility and colonisation of the chicken gastrointestinal tract - Kanji, Alpa; Jones, M.A.; Maskell, Duncan J.; Grant, Andrew J. (Elsevier, 2015)
Campylobacter jejuni is the leading cause of foodborne bacterial gastroenteritis worldwide. Although the mechanisms by which C. jejuni causes disease are not completely understood, the presence of functional flagella appears to be required for colonisation of the gastrointestinal tract of humans and animals. Therefore much attention has been given to understanding the synthesis and role of flagella in C. jejuni. In this study we report insights into the function of PflB that is essential for Campylobacter motility. We have explored the function of this gene by constructing deletion mutants in C. jejuni strains NCTC11168 and M1, in the genes cj0390 and CJM1_0368, respectively. The mutants were non-motile yet assembled flagella that appeared structurally identical to the wild type. Furthermore the protein is required for C. jejuni colonisation of caeca in a two-week old chicken colonisation model.